2016
DOI: 10.1097/md.0000000000002528
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Adolescent HIV Vaccination in South Africa

Abstract: Despite comprising 0.7% of the world population, South Africa is home to 18% of the global human immunodeficiency virus (HIV) prevalence. Unyielding HIV subepidemics among adolescents threaten national attempts to curtail the disease burden. Should an HIV vaccine become available, establishing its point of entry into the health system becomes a priority. This study assesses the impact of school-based HIV vaccination and explores how variations in vaccine characteristics affect cost-effectiveness.The cost per q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Transition probabilities are summarised in Table 1. Self-reported incidence data of NSIs suffer from significant under-reporting, so Transition probabilities* Annual attrition rate 0.031 0.024 -0.038 [44] Annual probability of NSI HIV transmission 0.0023 Beta [41] Effectiveness PEP 0.81 0.43 -0.94 [42,43] HIV progression Asymptomatic to symptomatic 0.32 [48] Symptomatic to AIDS 0.20 [48] Annual mortality rate (probability*) Asymptomatic HIV 0.0148 [49] Symptomatic HIV 0.0169 [49] AIDS 0.21 [49] NSI = needlestick injury; PEP = post-exposure prophylaxis. *1 = absolute certainty an event will occur, 0 = absolute certainty an event will not occur.…”
Section: Transition Probabilitiesmentioning
confidence: 99%
“…Transition probabilities are summarised in Table 1. Self-reported incidence data of NSIs suffer from significant under-reporting, so Transition probabilities* Annual attrition rate 0.031 0.024 -0.038 [44] Annual probability of NSI HIV transmission 0.0023 Beta [41] Effectiveness PEP 0.81 0.43 -0.94 [42,43] HIV progression Asymptomatic to symptomatic 0.32 [48] Symptomatic to AIDS 0.20 [48] Annual mortality rate (probability*) Asymptomatic HIV 0.0148 [49] Symptomatic HIV 0.0169 [49] AIDS 0.21 [49] NSI = needlestick injury; PEP = post-exposure prophylaxis. *1 = absolute certainty an event will occur, 0 = absolute certainty an event will not occur.…”
Section: Transition Probabilitiesmentioning
confidence: 99%
“…Subsequent analyses for tenofovir gel estimated a cost of less than US$300 per DALY averted (Terris-Prestholt and others 2014), assuming effectiveness. Similarly, the incremental cost-effectiveness for an HIV vaccine, also assuming effectiveness, was US$43 per DALY averted (Moodley, Gray, and Bertram 2016). A study of female condom program modeling found a low of US$107 per DALY averted in Zimbabwe and a high of US$303 per DALY averted in Mozambique, assuming that condoms would be used and would be effective (Mvundura and others 2015).…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%
“…Such vaccine could be seen as a first-generation product that must still be improved upon in order to fundamentally transform the HIV epidemic. Mathematical models [23,19,39,6,18,26,25,16,31,5,24] suggest that the first-generation vaccine would be useful and cost-effective to roll out, but that its overall impact will be modest. Here, we explore what factors contribute collectively to limiting the impact of such a vaccine.…”
Section: Introductionmentioning
confidence: 99%